Changing Notions of Nursing Care in Socio-Cultural and Psychological Interventions: A Systematic Review - Bhandari, Bhagwati (NPRC Journal of Multidisciplinary Research, 2025)
Although historically important in clinical environments, nursing care is evolving through outpatient concerns, community health strategies and health promotion approaches. Taking this outset, this paper is developed as a systematic review endorsing secondary literature from scientific research. It looks at the progress made in the nursing roles and has compiled evidence data on non-clinical practices, including community health promotion, mental health, and telehealth interventions. These results draw attention to the roles' increasing importance in responding to the social determinants of health and promoting sustainable healthcare delivery. Several issues are critical, including lack of policy support, inadequate professional development in non-clinical competencies, and organizational culture barriers. The review, therefore, underlines the need to reclaim the nursing education curriculum to include non-clinical approaches and collaborations with other professions for effective and efficient care provision. When these challenges are met, and concerning technological developments, nursing can extend its frontiers to other realms than hospitals. Further studies should try to understand follow-up impacts and the generalization possibility of non-healthcare-oriented approaches to properly recognize the full potential of non-clinical interventions for enhancing global health equity and improving the quality of the population’s lives.